The Controversies and Challenges in the Management of Twin Pregnancy: From the Perspective of International Federation of Gynecology and Obstetrics Guidelines. Issue 4 (15th October 2022) - Liu, Jingyu; Liu, Quanrui; Zhao, Jingya; Li, Danlun; Zhou, Yi
Abstract: The rate of multiple pregnancy is increasing, mainly because of the widespread use of assisted reproduction techniques and families' desire for twins. Twin pregnancy accounts for a higher risk of chromosomal abnormalities, structural malformations, and neonatal adverse events than singleton pregnancy. The presence of artery-vein anastomoses, unbalanced placenta sharing, and abnormal cord insertion in monochorionic twins is associated with twin complications such as twin-to-twin transfusion syndrome, selective intrauterine growth restriction, and twin anemia polycythemia sequence. Although many guidelines and studies have established and improved the processes about the antenatal surveillance and management of twin pregnancy, they also raise more controversies and challenges. This review aims to highlight the international consensus on the antenatal care of twin pregnancies and analyze the controversies and predicaments based on the published International Federation of Gynecology and Obstetrics guidelines and research.